Home Broadband and Human Capital Formation - Rosa Sanchis-Guarner; José Montalbán; Felix Weinhardt (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper estimates the effect of home high-speed internet on national test scores of students at age 14. We combine comprehensive information on the telecom network, administrative student records, house prices and local amenities in England in a fuzzy spatial regression discontinuity design across invisible telephone exchange catchment areas. Using this strategy, we find that increasing broadband speed by 1 Mbit/s increases test scores by 1.37 percentile ranks in the years 2005-2008. This effect is sizeable, equivalent to 5% of a standard deviation in the national score distribution, and not driven by other technological mediating factors or school characteristics.
Keywords: J24; I21; I28; D83; 330; broadband; education; student performance; spatial regression discontinuity